Privacy in mini-drone based video surveillance - Bonetto, Margherita; Korshunov, Pavel; Ramponi, Giovanni; Ebrahimi, Touradj (2015 11th IEEE International Conference and Workshops on Automatic Face and Gesture Recognition (FG), 2015)
Mini-drones are increasingly used in video surveillance. Their areal mobility and ability to carry video cameras provide new perspectives in visual surveillance which can impact privacy in ways that have not been considered in a typical surveillance scenario. To better understand and analyze them, we have created a publicly available video dataset of typical drone-based surveillance sequences in a car parking. Using the sequences from this dataset, we have assessed five privacy protection filters via a crowdsourcing evaluation. We asked crowdsourcing workers several privacy- and surveillance-related questions to determine the tradeoff between intelligibility of the scene and privacy, and we present conclusions of this evaluation in this paper.